Aggregate stability of Alfisols root zone upon turfgrass treatment - Rahayu Rahayu; Jauhari Syamsiyah; Laila Nikmatus Sa'diyah (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2020)
Soil degradation mostly occurs on land where a lack of surface coverage results in soil-aggregate destruction due to heavy rainfall. Turfgrass is an ornamental plant and covers the soil surface and, thus, potentially improves soil-aggregate stability. This study determined the potential of some summer grasses to improve soil-aggregate stability and was a pilot experiment using six turfgrass species: Paspalum vaginatum; middle-leaf Zoysia sp.; Cynodon dactylon; coarse-leaf Zoysia sp.; Axonopus compressus; Zoysia matrella. Turfgrasses were planted using stolons in a 0.6 m2 plot unit with 5 cm x 5 cm space. Lawn maintenance included irrigation, fertilizing, and weeding. Soil characteristics were observed six months after planting and showed that turfgrass increased the soil-aggregate index from 42.3% to 83.0% in control, and carbon particles measuring 6.4 μm from 28.3% to 63.0%.